Bagong barangay housing project an experiment in social housing - Ancog, Amelia C. (1978)
A survey on the Bagong Barangay Housing Project (BBHP) was conducted to describe and analyze the residents' perception of the Project's livability and the control exercised by the housing staff in the discharge of their administrative functions. Livability is operationalized in terms of three components: privacy, availability and accessibility of facilities and community relationships. The findings reveal that livability requirements are met and that viable community organizations exist in the BBHP Moreover, the survey discloses that the staff's control functions are not "perceived" by the residents. This non-perception of controls contributes to the introduction of physical alterations and innovations which enhances the dwelling units' livability.
Keywords: Housing; Housing research; Public housing aspects; Bagong Barangay Housing Project (BBHP)